Convergence of naïve coders and participant report ratings of attachment to a former partner: When we should be me. (March 2019) - Borelli, Jessica L.; Sbarra, David A.; Mehl, Matthias
Using a Brunswik lens framework, this study examined whether lay observers could accurately detect participants' attachment to a former partner following romantic breakup or divorce. We predicted that the ratings of post-breakup attachment (completed after reading participants' transcribed stream-of-consciousness discussions of the recent separation) would be associated with participants' self-reported ratings of attachment to a former partner and that participants' natural language use in their narratives would act as the behavioral residue explaining these associations. To enhance the generalizability of our findings, we explored our hypotheses in two samples of adults who had recently undergone romantic relationship dissolutions—people experiencing non-marital breakups ( N = 161) and divorce ( N = 132). Consistent with hypotheses, in both samples, naïve judges generated assessments of participant attachment that were (a) reliable, (b) strongly associated with participants' own attachment ratings, and (c) associated with participant breakup-related distress. Of the linguistic cues we examined as behavioral residue, only we-talk (first person plural pronoun use) operated indirectly to link rater and participant attachment scores. We discuss the implications of this work for a deeper understanding of attachment to former romantic partners and for using person-perception paradigms to study attachment relationships.